PENGUASAAN MODEL PENILAIAN HASIL BELAJAR DALAM MERAIH MUTU SEKOLAH OLEH KEPALA SEKOLAH MELALUI SUPERVISI AKADEMIK DI SMPN 41 MEDAN - Lukman Pardede; Dewi Lestari Pardede (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
This study aims at determining the extent of the application of academic supervision in improving the performance of school principals in applying the learning outcomes assessment model at SMPN 41 Medan. Assessment consists of external assessments and internal assessments. External assessments are assessments made by other parties who do not carry out the learning process. External assessments are carried out by an institution, both domestic and foreign, intended among other things to control quality. While internal assessments are assessments planned and carried out by the teacher during the learning process. Class assessment is part of an internal assessment (internal assessment) to determine student learning outcomes towards mastery of competencies taught by the teacher. The aim is to assess the level of achievement of student competencies that are carried out when learning takes place and the end of learning. The assessment of student learning outcomes is carried out by the teacher to monitor the process, progress, development of student learning outcomes in accordance with their potential and expected abilities on an ongoing basis. Assessment can also provide feedback to teachers in order to improve planning and learning processes. In this surveillance action research carried out in 3 cycles, the results of the actions taken are proven to improve the quality of schools by achieving ideal standards. From 64.25% in Cycle 1, it can be increased to 73.75% in Cycle II, and in the third cycle to 83.25% and has met the ideal standard.